2020
DOI: 10.3390/su12072784
|View full text |Cite
|
Sign up to set email alerts
|

Examining Structural Relationships among Brand Experience, Existential Authenticity, and Place Attachment in Slow Tourism Destinations

Abstract: Understanding how tourists’ brand experiences impact their existential authenticity, and the role of existential authenticity in the formation mechanism of place attachment to the destination, are key issues for the marketing of a destination. The current study examines the relationship between tourists’ experience, existential authenticity, and place attachment, and the indirect effect of existential authenticity on the relationship between destination brand experience and place attachment from the oriental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 82 publications
(222 reference statements)
4
46
0
Order By: Relevance
“…It was also suggested that the bootstrap ML (maximum likelihood) and bias-corrected 95% confidence intervals (CI) should also be applied in the bootstrap method in AMOS [91,93,94]. Additionally, based on some tourism studies using the bootstrap method [88,[95][96][97], the current study chose 10,000 resamples for the bootstrap method. The results of the fit indices indicated that all the indicators corresponded well to the construct to which they belong.…”
Section: Measurement Modelmentioning
confidence: 99%
“…It was also suggested that the bootstrap ML (maximum likelihood) and bias-corrected 95% confidence intervals (CI) should also be applied in the bootstrap method in AMOS [91,93,94]. Additionally, based on some tourism studies using the bootstrap method [88,[95][96][97], the current study chose 10,000 resamples for the bootstrap method. The results of the fit indices indicated that all the indicators corresponded well to the construct to which they belong.…”
Section: Measurement Modelmentioning
confidence: 99%
“…The former refers to the sensory enjoyment and self-realization of individuals in performing tourism activities, whereas the latter refers to the natural and equal interpersonal interaction between tourists and other persons in tourism destination [1]. It is worth noticing that the over-generalization of existential authenticity should be avoided [13][14][15][16] because not all Sustainability 2021, 13, 3716 2 of 14 tourism experiences can enhance tourists in attaining a state of "authentic being" [17]. In this regard, Kirillova found that the influence of existential authenticity in the settings of cultural heritage, sightseeing, theme parks, backpacking, and volunteer tourism is much more conspicuous and significant than in other tourism contexts [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars found that the object-based authenticity positively affects tourists' loyalty while existential authenticity has no significant influence [9,21]. However, other scholars suggested conflicting findings [8,15,16]. Likewise, the influence of existential authenticity on loyalty is equally under-researched.…”
Section: Introductionmentioning
confidence: 99%
“…Study the brand experience and the structural relationship between authenticity and place attachment in slow travel destinations (Shang, 2020) intangible and Space…”
Section: International Research Status and Trendsmentioning
confidence: 99%